2021
DOI: 10.1177/10600280211025042
|View full text |Cite
|
Sign up to set email alerts
|

Potential Dexamethasone–Direct Oral Anticoagulant Drug Interaction: Is This a Concern in COVID?

Abstract: Objective To evaluate the literature on a potential dexamethasone–direct oral anticoagulant (DOAC) drug interaction and provide management considerations with COVID hypercoagulability. Data Sources A search of EMBASE, PubMed, and Google Scholar (January 1990 to May 2021), limited to the English language, using applicable search terms resulted in 137 articles, with 21 relevant articles included. Regulatory agency and clinical guidance documents were also reviewed. Study Selection and Data Extraction Included ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…Moreover, it is plausible that CYPs metabolic activity is downregulated during ARDS and other severely inflammatory states, resulting in an altered pharmacokinetic clearance and interaction. Therefore, one may recommend the avoidance of DOACs (especially apixaban and rivaroxaban) in admitted patients on dexamethasone until high-quality evidence is becoming available [ 122 ]. A small study in patients showed that peak DOAC levels on dexamethasone were below the expected range in 33.3%, of whom about two-thirds had also low levels without dexamethasone [ 123 ].…”
Section: Challenges With Current Antithrombotic Treatmentmentioning
confidence: 99%
“…Moreover, it is plausible that CYPs metabolic activity is downregulated during ARDS and other severely inflammatory states, resulting in an altered pharmacokinetic clearance and interaction. Therefore, one may recommend the avoidance of DOACs (especially apixaban and rivaroxaban) in admitted patients on dexamethasone until high-quality evidence is becoming available [ 122 ]. A small study in patients showed that peak DOAC levels on dexamethasone were below the expected range in 33.3%, of whom about two-thirds had also low levels without dexamethasone [ 123 ].…”
Section: Challenges With Current Antithrombotic Treatmentmentioning
confidence: 99%
“…Drugs employed for COVID-19, particularly those interacting with CYP3A4 and P-gp metabolic pathways, may affect the pharmacokinetic and pharmacodynamic profiles of DOACs, thereby altering their anticoagulant activity [6][7][8]. Dexamethasone, an inducer of both CYP3A4 and P-gp, may reduce bioavailability and increase clearance of DOACs, potentially leading to reduced plasma concentrations [9][10][11]. Although it remains possible that a longer exposure or higher doses of dexamethasone would result in clinically relevant effects, our data, which confirm and expand previous preliminary findings, seem to be reassuring as they suggest that relevant systematic interactions, if any, are unlikely [13].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, dexamethasone, administered intravenously at a dose of 6 mg, has become standard-of-care for the treatment of hypoxemic COVID-19 patients [4]. Whether concomitant administration of DOACs and dexamethasone, a well-known inducer of both CYP3A4 and P-gp [9,10], results in lower DOAC concentrations that may be clinically relevant is currently uncertain [6,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone, prednisone, and other corticosteroids may increase the bleeding risk at upper GI level; thus, a potential PD interaction is predicted (Table 10). In addition, dexamethasone may induce P-gp and partially affect the anticoagulant action of DOACs, although clinical data suggesting that dexamethasone is a P-gp inducer are limited and indirect [113,114].…”
Section: Potential Drug-drug Interaction With Antineoplastic and Immu...mentioning
confidence: 99%